(untitled) (Central Medical College Journal, 2025)
Background: Obsessive-compulsive disorder (OCD) is a long-term mental health condition marked by persistent, intrusive thoughts and repetitive actions performed to alleviate anxiety. It can severely disrupt daily activities and diminish quality of life. Individuals with OCD frequently encounter difficulties in social, occupational, and personal domains due to the overwhelming and time-intensive nature of their symptoms. This study aimed to analyze the demographic and clinical features of obsessive-compulsive disorder patients. Methods: This descriptive cross-sectional study was carried out in the Department of Psychiatry at Community Based Medical College Bangladesh, Mymensingh, over six months from January to June 2021. A total of 83 individuals diagnosed with obsessive-compulsive disorder (OCD) were purposively selected as study participants. Data collection was performed using a structured, pre-designed questionnaire, and the analysis was conducted utilizing MS Office tools. Results: Nearly one-third of participants (32.5%) was aged 46 to 60 years and exhibited cleaning symptoms (36.1%). The gender and residency distribution were nearly balanced, with 66.3% of participants being married. The mean total and the average duration of illness was 5.9 ± 4.7 years. A history of OCD (Family) was observed among 27.7% of participants. In terms of comorbidities, major depressive disorder was present in 51.8% of participants, with social phobia (26.5%), panic disorder (24.1%), and substance dependence (20.5%) also affecting more than 20% of participants. Conclusion: Aged married individuals are prone to obsessive-compulsive disorder, with major types of depressive disorder as the most prevalent comorbidity. Many OCD cases involve a family history and a habit of cleaning. Central Medical College Journal Vol 8 No 2 July 2024 Page: 54-57